Impact of Caffeine on Aquatic Ecosystems: Assessing Trophic-Level Biological Responses - Sara Rodrigues; Rita S. Alves; Sara C. Antunes (Journal of Xenobiotics, 2025)
This study evaluates the effects of caffeine (CAF) on the bacteria Aliivibrio fischeri, the microalga Raphidocelis subcapitata, the macrophyte Lemna minor, and the larvae of Chironomus riparius, aiming to understand its environmental impact and contribution to ecological risk assessment. Bioluminescence inhibition in A. fischeri (EC50 = 998.5 mg/L) and growth inhibition in R. subcapitata and L. minor (EC50 = 60.1 mg/L and EC50 = 649.2 mg/L, respectively) were observed. For L. minor, reduced catalase (CAT) activity and non-linear responses in glutathione S-transferases (GSTs) were recorded. No significant changes were observed in proline, malondialdehyde (MDA), and pigment contents. In C. riparius, acute mortality (LC50 = 644.5 mg/L) was observed, and growth was significantly affected after 10 days of CAF exposure (EC50 = 81.62 mg/L for fresh biomass). After 10 days of exposure, there was an increase in CAT activity and thiobarbituric acid reactive substances, with TBARS levels both at concentrations ≥82.64 mg/L, and a decrease in GSTs (92.18 mg/L) and acetylcholinesterase (AChE) (≤62.09 mg/L) activities of C. riparius. The results show that CAF exposure affects organisms’ metabolic and physiological functions, with varying sensitivities among species, potentially leading to ecological disturbances in aquatic ecosystems. The hazardous concentration for 5% of species was 4.42 mg/L. Long-term studies are necessary to understand the risk of caffeine under more realistic scenarios.